Uterine Lipoleiomyoma: Review of literature and Two Case Reports - Onak Kandemir, Nilüfer; Barut, Figen; Bektaş, Sibel; Bahadır, Burak; Doğan Gün, Banu; Kökten, Neslihan; Gökçe, Havva; Barut, Aykut; Özdamar, Şükrü Oğuz (Gynecology Obstetrics & Reproductive Medicine, 2011)
Lipoleiomyoma is uncommon mesenchymal neoplasm which contains mature adipose tissue and smooth muscle components. Its prevalence among all uterine leiomyomas varies between 0,03-0,2% . In the current study, we present two lipoleiomyoma cases alongside clinical and histopathological data as well as information on etiopathogenesis. The first case was a 59-year-old female patient presented with postmenopausal hemorrhage and she was subjected to hysterectomy upon clinical diagnosis of myoma uteri. Second case was a 45-year-old woman who presented with postcoital hemorrhage. Polypoid lesion which had a uterine cervix localization was excised. Histopathological examination of the operation materials belonging to these two cases, revealed intramural (first case) and submucosal (second case) lipoleiomyoma, both of which had a varying degree of adipose tissue and smooth muscle components. In leiomyoma cases, detection of other heterologous components alongside smooth muscle cells, is an uncommon event. Presence of an adipose tissue higher than 10%, should indicate lipoleiomyoma.